Experimental Study on the Mechanical and Permeability Properties of Lining Concrete Under Different Complex Stress Paths - Liu, Wenhao; Peng, Huihua; Guo, Pengyu; Chen, Shengwei; Liu, Wei; Kang, Yanfei (Frontiers in Earth Science, 2022)
A promising large-scale energy storage is underground compressed air energy storage (CAES) in lined rock caverns. To ensure the safety and stability of storage caverns because of the influence of periodic injection during production, it is crucial to understand the mechanical behavior of lining concrete under different complex stress paths. In this study, three types of uniaxial compressive fatigue test and uniaxial creep test were conducted on concrete. The following conclusions were obtained from the results. (1) The irreversible deformation after the interval was larger than that before the interval in the discontinuous multi-step cyclic loading (DMCL) test. (2) Loading velocity significantly influenced concrete fatigue, and the irreversible deformation in the cycle of low loading velocity was greater than that in the cycle of high loading velocity. (3) The residual strain increased with an increase in stress level. (4) The creep strain increased with an increase in stress level during the multi-step creep loading test; the fractional derivative results were more consistent with the experimental results. (5) The permeability of concrete increased rapidly under the influence of an external force when the stress level exceeded 0.73.